Financial Coping in Facing Household Financial Crisis during Covid-19 Pandemic (Case Study on Employees of PT. Sun Star Motor Banyumanik) - Joko Wijaya Tjang; Titi Susilowati Prabawa (Budapest International Research and Critics University, 2022)
The automotive industry plays a significant role in the Indonesian economy. However, the automotive industry is one of the manufacturing sectors most affected by the Covid-19 pandemic. PT. Sun Star Motor Banyumanik also experienced a drastic decline in sales of up to 60% in May 2020. As a result, the company terminated 20 employees, and a reduction of 25% of the total monthly salary was also applied to employees who were still employed maintained. This paper aims to analyze the financial coping strategies carried out by employees in dealing with the domestic financial crisis during the COVID-19 pandemic. In this paper, the author uses a constructive qualitative approach through observation, in-depth interviews, and document studies to elaborate on the financial coping strategies of PT. Sun Star Motor Banyumanik in the face of the COVID-19 pandemic. The data collected were analyzed by thematic analysis through grouping based on themes which were then synthesized. The results of our research show that the employees studied were able to survive by carrying out financial copings are income diversification with running a side business, saving expenses, and delaying credit payments. Employees still need long-term innovations to be able to anticipate changes due to the pandemic